Scandium negative electrode material and preparation method and application thereof

Through gel-heat compression domain-limited curing and surface oxidant modification technology, high-purity and high-stability scandium oxide nanoparticles were prepared, which solved the problems of difficulty in controlling, high risk and difficulty in removing impurities of existing scandium oxide preparation methods, and achieved efficient preparation of negative electrode materials suitable for lithium-ion secondary batteries.

CN119683670AActive Publication Date: 2025-03-25LIYANG TIANMU PILOT BATTERY MATERIAL TECH CO LTD

Patent Information

Application Number
CN202311249961.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-25
Publication Date
2025-03-25
Estimated Expiration
2043-09-25

AI Technical Summary

Technical Problem

The existing scandium oxide preparation methods have problems such as difficult control, high risk, difficult to remove residual alkali and difficult to effectively remove impurities, resulting in the prepared scandium oxide material that cannot meet the requirements of lithium-ion secondary battery negative electrode materials.

Method used

Scandium oxide nanoparticles are prepared by gel-heat compression domain-limiting curing, and the gel is formed by the mutual dissolution of scandium-containing compounds and coagulation agents, and the scandium ion dispersion is increased during the hot compression curing process to form a dense material. At the same time, by modifying the surface oxidant solution, carbon elements and impurities are removed to improve the purity of the material.

Benefits of technology

The uniform dispersion, high purity and high stability of scandium-based negative electrode materials are achieved, the process is simplified, the safety is improved, and the material is suitable for the industrial application of lithium-ion secondary battery negative electrode materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119683670A_ABST
    Figure CN119683670A_ABST
Patent Text Reader

Abstract

The embodiment of the invention relates to a scandium-based negative electrode material and a preparation method and application thereof. The preparation method comprises the following steps: dissolving a scandium-containing compound in deionized water to prepare a homogeneous solution, adding a coagulator, and stirring and mixing to obtain a first solution; placing the first solution in a heating device, and enabling a molecular chain of the coagulator to be broken and dissolved to form a cross-linked sol containing a scandium ion solution; standing the sol at room temperature to obtain solid gel; carrying out hot-pressing curing on the solid gel to obtain a cured sample with uniformly dispersed scandium ions; placing the cured sample in a tubular furnace for heat treatment to obtain a scandium nitride-containing carbon matrix, then placing the scandium nitride-containing carbon matrix in a surface oxidant solution for soaking to modify the scandium nitride-containing carbon matrix, washing the modified sample with water, performing suction filtration, and drying to obtain a modified scandium-based carbon matrix; or directly washing and filtering the scandium nitride-containing carbon matrix, and drying to obtain an unmodified scandium-based carbon matrix; and finally, calcining in an oxidizing atmosphere to remove residual carbon so as to obtain the scandium oxide nanoparticles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of negative electrode materials for new energy batteries, and in particular to a scandium-based negative electrode material and a preparation method and application thereof. Background Art

[0002] The development of green, environmentally friendly and high-energy-density lithium-ion secondary batteries has practical significance for the development of new energy technologies. As the core material, the negative electrode material can affect the capacity, cycle and charge-discharge performance of lithium-ion batteries. Scandium oxide nanoparticles present a cubic structure of rare earth sesquioxides, with good mechanical properties, optical properties, electrical properties and thermal conductivity, and have broad application prospects in the fields of ceramic materials, high-temperature superconducting materials, high-performance magnetic materials and catalytic materials. In addition, due to the excellent thermal stability, chemical stability, high dielectric constant and low dielectric loss of scandium oxide, it has become a potential functional material for the preparation of high-performance lithium-ion secondary battery negative electrode materials.

[0003] The currently commonly used method for preparing scandium oxide in industry is to react a strong alkali with a scandium salt to generate a precipitate to obtain scandium hydroxide, which is then thermally decomposed to form scandium oxide. However, this reaction is difficult to control, highly dangerous, and the residual alkali is difficult to remove. It is easy to introduce additional metal ions during the preparation. The scandium oxide material prepared by this method is not well suitable for lithium-ion secondary battery negative electrode materials. The method that relies on the thermal decomposition reaction of existing scandium salts to obtain scandium oxide is difficult to control the reaction process, and impurities cannot be effectively removed, which often does not meet the requirements for the application of negative electrode materials and affects the electrochemical performance. Therefore, it is necessary to develop a method for preparing a scandium-based negative electrode material that is safer and more convenient for industrial application, so as to obtain a lithium battery negative electrode material with high capacity, high stability and commercial application. Summary of the invention

[0004] The purpose of the present invention is to provide a scandium-based negative electrode material and a preparation method and application thereof. The method prepares scandium oxide nanoparticles by gel-hot pressing confined solidification. When the scandium-containing compound and the coagulant are mutually dissolved and a gel is formed at room temperature, the overall dispersion and uniformity of the scandium-containing compound molecules are significantly improved, and the intermolecular forces and pressures generated during the evaporation of the solvent molecules during hot pressing solidification increase the dispersion of the scandium ions while the material is solidified, forming a densely structured material. The scandium-based negative electrode material synthesized by the technical solution of the present invention is evenly dispersed and has high purity. The preparation method has a simple synthesis process and high safety, and can be mass-produced using existing equipment.

[0005] To this end, in a first aspect, an embodiment of the present invention provides a method for preparing a scandium-based negative electrode material, comprising:

[0006] Dissolving the scandium-containing compound in deionized water to prepare a homogeneous solution with a mass concentration of 10%-40%, adding a coagulant to the homogeneous solution, stirring and mixing to obtain a first solution;

[0007] Placing the first solution in a heating device, heating it to 80° C.-100° C., and keeping it warm for 0.5 h-1 h, so that the molecular chains of the coagulant are broken and dissolved, so that the first solution forms a cross-linked sol containing a scandium ion solution; leaving the sol to stand at room temperature to obtain a solid gel;

[0008] hot-pressing the solid gel to obtain a solidified sample in which scandium ions are uniformly dispersed;

[0009] The solidified sample is placed in a tube furnace, and the temperature is raised to 700° C.-1000° C. at 2° C. / min-10° C. / min in a nitrogen atmosphere, and the temperature is kept for 2 h-6 h to obtain a carbon matrix containing scandium nitride;

[0010] The carbon matrix containing scandium nitride is modified by soaking the carbon matrix containing scandium nitride in a surface oxidant solution with a concentration of 60%-80% at 20°C-60°C for 1h-6h, washing the modified sample with water, filtering it to a neutral pH, and drying it to obtain a modified scandium-based carbon matrix; or the carbon matrix containing scandium nitride is directly washed with water, filtered it to a neutral pH, and dried to obtain an unmodified scandium-based carbon matrix; wherein oxygen-containing functional groups are generated on the carbon matrix of the modified scandium-based carbon matrix;

[0011] The modified scandium-based carbon matrix or the unmodified scandium-based carbon matrix is ​​heated to a set temperature at 2°C / min-10°C / min in an oxidizing atmosphere, and sintered for 2h-6h to remove residual carbon in the modified scandium-based carbon matrix to obtain scandium oxide nanoparticles.

[0012] Preferably, the scandium-containing compound includes: one or more of scandium chloride, scandium nitrate, scandium sulfate, scandium oxalate and hydrates thereof;

[0013] The coagulant includes: one or more of agar, carrageenan, gelatin, gum arabic or pectin;

[0014] The mass ratio of the scandium element in the scandium-containing compound to the coagulant is 1:2-1:10.

[0015] Preferably, the standing time is 8-20 hours;

[0016] The hot pressing pressure is 10MPa-30MPa, the temperature is 150°C-250°C, and the hot pressing time is 0.5h-2h.

[0017] Preferably, the surface oxidant solution specifically includes one or more of potassium permanganate solution, nitric acid solution, and sulfuric acid solution;

[0018] The chemical reactions occurring during the modification of the carbon matrix containing scandium nitride include: the scandium nitride in the carbon matrix containing scandium nitride undergoes an oxidation-reduction reaction with the surface oxidant solution to generate one or more of Sc2(SO4)3, Sc(NO3)3, and Sc2O3; and oxygen-containing functional groups are generated on the surface of the carbon matrix.

[0019] Further preferably, when the modified scandium-based carbon matrix is ​​sintered, when the surface oxidant solution used includes a sulfuric acid solution, the set temperature is 800° C.-1000° C.;

[0020] When the surface oxidant solution used is potassium permanganate solution and / or nitric acid solution, the set temperature is 600° C.-800° C.;

[0021] The oxidizing atmosphere includes air or oxygen;

[0022] In an oxidizing atmosphere, in the modified scandium-based carbon matrix, residual carbon on the carbon matrix is ​​oxidized by oxygen to generate carbon dioxide. At the same time, Sc2(SO4)3 or Sc(NO3)3 present in the modified scandium-based carbon matrix is ​​thermally decomposed to form the scandium oxide nanoparticles.

[0023] Further preferably, when the surface oxidant solution used is a potassium permanganate solution, the by-product of the redox reaction also includes MnO2, and the MnO2 exists on the surface of the scandium-based negative electrode material after the sintering as a negative electrode coating layer of the scandium oxide nanoparticles and / or exists in the scandium-based negative electrode material as an additive.

[0024] Preferably, when the unmodified scandium-based carbon matrix is ​​sintered in an oxidizing atmosphere, residual carbon on the carbon matrix in the unmodified scandium-based carbon matrix is ​​oxidized by oxygen to generate carbon dioxide, and at the same time, ScN present in the unmodified scandium-based carbon matrix is ​​oxidized to form the scandium oxide nanoparticles.

[0025] In a second aspect, an embodiment of the present invention provides a scandium-based negative electrode material prepared by the preparation method described in the first aspect.

[0026] In a third aspect, an embodiment of the present invention provides a negative electrode plate for a lithium battery, comprising the scandium-based negative electrode material described in the second aspect.

[0027] In a fourth aspect, an embodiment of the present invention provides a lithium battery, comprising the lithium battery negative electrode sheet described in the third aspect above.

[0028] The preparation method of the scandium-based negative electrode material provided in an embodiment of the present invention prepares scandium oxide nanoparticles by gel-hot pressing confined solidification. When the scandium-containing compound and the coagulant are mutually dissolved and a gel is formed at room temperature, the overall dispersion and uniformity of the scandium-containing compound molecules are significantly improved, and the intermolecular forces and pressures generated during the evaporation of the solvent molecules during hot pressing solidification increase the dispersion of the scandium ions while the material is solidified, forming a densely structured material. By modifying the surface oxidant solution, oxygen-containing functional groups are generated on the carbon matrix of the modified scandium-based carbon matrix, and in the subsequent oxidation sintering and carbon removal process steps, it is easier to fully remove carbon elements and carry away impurities in the material at the same time, so that the resulting material has a higher purity. The scandium-based negative electrode material synthesized by the technical solution of the present invention is evenly dispersed and has high purity. The preparation method has a simple synthesis process and high safety, and can be mass-produced using existing equipment. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 A flow chart of a method for preparing a scandium-based negative electrode material provided by an embodiment of the present invention;

[0030] Figure 2 A flow chart of another method for preparing a scandium-based negative electrode material provided in an embodiment of the present invention. DETAILED DESCRIPTION

[0031] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments.

[0032] The present invention provides a method for preparing a scandium-based negative electrode material. Figure 1 As shown, the preparation method comprises:

[0033] Step 110, dissolving the scandium-containing compound in deionized water to prepare a homogeneous solution with a mass concentration of 10%-40%, and adding a coagulant to the homogeneous solution, stirring and mixing to obtain a first solution;

[0034] The scandium-containing compounds include: one or more of scandium chloride, scandium nitrate, scandium sulfate, scandium oxalate and their hydrates;

[0035] The solidifying agent includes: one or more of agar, carrageenan, gelatin, gum arabic or pectin;

[0036] The mass ratio of the scandium element in the scandium-containing compound to the coagulant is 1:2-1:10.

[0037] Step 120, placing the first solution in a heating device, heating it to 80°C-100°C, and keeping it warm for 0.5h-1h, so that the molecular chains of the coagulant are broken and dissolved, so that the first solution forms a cross-linked sol containing the scandium ion solution; and leaving the sol to stand at room temperature to obtain a solid gel;

[0038] The standing time is 8-20 hours.

[0039] Step 130, hot pressing the solid gel to obtain a solidified sample with evenly dispersed scandium ions;

[0040] The hot pressing pressure is 10MPa-30MPa, the temperature is 150℃-250℃, and the hot pressing time is 0.5h-2h.

[0041] Step 140, placing the solidified sample in a tube furnace, heating it to 700°C-1000°C at 2°C / min-10°C / min in a nitrogen atmosphere, and keeping the temperature for 2h-6h to obtain a carbon matrix containing scandium nitride;

[0042] During this process, the organic components in the gel are carbonized at high temperature to form a carbon matrix.

[0043] Step 150, soaking the carbon matrix containing scandium nitride in a surface oxidant solution with a concentration of 60%-80% at 20° C.-60° C. for 1 h-6 h to modify the carbon matrix containing scandium nitride, washing the modified sample with water, filtering it to a neutral pH, and drying it to obtain a modified scandium-based carbon matrix;

[0044] Specifically, the surface oxidant solution includes one or more of potassium permanganate solution, nitric acid solution, and sulfuric acid solution;

[0045] The chemical reactions occurring during the modification of the carbon matrix of scandium nitride include: the scandium nitride in the carbon matrix containing scandium nitride undergoes an oxidation-reduction reaction with the surface oxidant solution to generate one or more of Sc2(SO4)3, Sc(NO3)3, and Sc2O3.

[0046] The specific reaction process may include but is not limited to the following reactions:

[0047] 2ScN+5H2SO4→Sc2(SO4)3+2NH4HSO4;

[0048] 2ScN+2KMnO4+5H2O→Sc2O3+2MnO2+2KNO3+10H + ;

[0049] One or more of ScN+4HNO3→Sc(NO3)3+NH4NO.

[0050] At the same time, oxygen-containing functional groups are generated on the carbon matrix.

[0051] Step 160 , raising the temperature of the modified scandium-based carbon matrix to a set temperature at 2° C. / min-10° C. / min in an oxidizing atmosphere, and sintering for 2 h-6 h to remove residual carbon in the modified scandium-based carbon matrix to obtain scandium oxide nanoparticles.

[0052] When the modified scandium-based carbon matrix is ​​sintered, when the surface oxidant solution used includes a sulfuric acid solution, the preferred setting temperature is 800° C.-1000° C.; when the surface oxidant solution used is a potassium permanganate solution and / or a nitric acid solution, the preferred setting temperature is 600° C.-800° C.;

[0053] Oxidizing atmospheres include air or oxygen;

[0054] In an oxidizing atmosphere, the residual carbon on the carbon matrix in the modified scandium-based carbon matrix is ​​oxidized by oxygen to generate carbon dioxide. At the same time, the Sc2(SO4)3 or Sc(NO3)3 present in the modified scandium-based carbon matrix is ​​thermally decomposed to form scandium oxide nanoparticles. The decomposition products of Sc(NO3)3 when thermally decomposed include scandium oxide (Sc2O3), gaseous nitrogen oxides and oxygen; the decomposition products of Sc2(SO4)3 when thermally decomposed include scandium oxide (Sc2O3), gaseous sulfur oxides and oxygen.

[0055] Because in the previous step, the modification of the surface oxidant solution causes oxygen-containing functional groups to be generated on the carbon matrix of the modified scandium-based carbon matrix, the oxidative sintering and carbon removal process in this step can more easily and fully react, removing the carbon element while also carrying away impurities in the material, making the resulting material of higher purity.

[0056] Furthermore, when the surface oxidant solution used is a potassium permanganate solution, the by-product of the redox reaction also includes MnO2, which exists on the surface of the scandium-based negative electrode material after sintering as a negative electrode coating of scandium oxide nanoparticles, helping to improve the safety and stability of the battery, and / or exists in the scandium-based negative electrode material as an additive, helping to stabilize the cycle performance of the battery, extend the life of the battery, and improve the capacity retention rate of the battery.

[0057] The present invention also provides another method for preparing a scandium-based negative electrode material. Figure 2 As shown, the preparation method comprises:

[0058] Step 210, dissolving the scandium-containing compound in deionized water to prepare a homogeneous solution with a mass concentration of 10%-40%, and adding a coagulant to the homogeneous solution, stirring and mixing to obtain a first solution;

[0059] The scandium-containing compounds include: one or more of scandium chloride, scandium nitrate, scandium sulfate, scandium oxalate and their hydrates;

[0060] The solidifying agent includes: one or more of agar, carrageenan, gelatin, gum arabic or pectin;

[0061] The mass ratio of the scandium element in the scandium-containing compound to the coagulant is 1:2-1:10.

[0062] Step 220, placing the first solution in a heating device, heating it to 80°C-100°C, and keeping it warm for 0.5h-1h, so that the molecular chains of the coagulant are broken and dissolved, so that the first solution forms a cross-linked sol containing the scandium ion solution; and leaving the sol to stand at room temperature to obtain a solid gel;

[0063] The standing time is 8-20 hours.

[0064] Step 230, hot pressing the solid gel to obtain a solidified sample with evenly dispersed scandium ions;

[0065] The hot pressing pressure is 10MPa-30MPa, the temperature is 150℃-250℃, and the hot pressing time is 0.5h-2h.

[0066] Step 240, placing the cured sample in a tube furnace, heating to 700°C-1000°C at 2°C / min-10°C / min in a nitrogen atmosphere, and keeping the temperature for 2h-6h to obtain a carbon matrix containing scandium nitride;

[0067] During this process, the organic components in the gel are carbonized at high temperature to form a carbon matrix.

[0068] Step 250, directly washing the carbon matrix containing scandium nitride with water, filtering until the pH is neutral, and drying to obtain an unmodified scandium-based carbon matrix;

[0069] Step 260, raising the temperature of the unmodified scandium-based carbon matrix to a set temperature at 2°C / min-10°C / min in an oxidizing atmosphere, and sintering for 2h-6h to remove residual carbon in the modified scandium-based carbon matrix to obtain scandium oxide nanoparticles.

[0070] The preferred setting temperature is 600°C-800°C;

[0071] Oxidizing atmospheres include air or oxygen;

[0072] In an oxidizing atmosphere, residual carbon on the carbon matrix in the unmodified scandium-based carbon matrix is ​​oxidized by oxygen to generate carbon dioxide, and at the same time, ScN existing in the unmodified scandium-based carbon matrix is ​​oxidized to form the scandium oxide nanoparticles.

[0073] 4ScN+3O2→2Sc2O3+N2.

[0074] In the preparation method of the scandium-based negative electrode material of the present invention, the scandium oxide nanoparticles are prepared by gel-hot pressing confined curing. The scandium compound is dispersed in the sol. When the gel is formed, the intermolecular dispersion force and mixing uniformity are significantly improved. The thermal curing is accompanied by the evaporation of the solvent molecules. The intermolecular forces and pressure generated make the scandium ions dispersed uniformly and the structure dense while the material is cured. The preparation method provided by the present invention optimizes the dispersion uniformity of the scandium-based material, the synthetic material has high purity, the preparation process is simple, and it can be mass-produced using existing equipment.

[0075] The scandium oxide nanoparticles prepared in the embodiment of the present invention have a cubic structure and obvious advantages in physical and chemical properties. Due to their excellent thermal stability, chemical stability, high dielectric constant and low dielectric loss, the material has a high reversible charge and discharge specific capacity and cycle stability, can exert excellent electrochemical properties, and has broad application prospects in the preparation of high-performance negative electrode materials.

[0076] The scandium-based negative electrode material prepared by the preparation method of the embodiment of the present invention can be used as a negative electrode material for lithium-ion batteries and applied to lithium battery pole pieces and lithium batteries.

[0077] In order to more clearly illustrate the purpose and advantages of the present invention, the present invention is further described below in conjunction with the embodiments. In addition, the embodiments described in the present invention are only partial embodiments. Based on the embodiments described in the present invention, all other embodiments obtained by those skilled in the art without creative work are within the protection scope of the present invention. In addition, it should be understood that these embodiments are only used for more detailed description and should not be understood as limiting the present invention in any form, that is, they are not intended to limit the protection scope of the present invention.

[0078] Example 1

[0079] This embodiment provides a method for preparing a scandium-based negative electrode material and a performance test thereof. The specific preparation process is as follows.

[0080] Weigh 200g of scandium nitrate and dissolve it in 300ml of deionized water to prepare a homogeneous solution with a concentration of 40%, add 389.3g of agar powder, and stir to mix evenly. Place the above solution in a constant temperature water bath, heat it to 80°C, and maintain it for 1h, so that the coagulant molecular chain breaks and dissolves, forming a cross-linked sol containing scandium ion solution. Subsequently, the sol is placed at room temperature and maintained for 12h to form a solid gel. The gel is placed under a hot press, maintaining the hot pressing curing pressure at 20MPa, the hot pressing temperature at 200°C, and the hot pressing time for 1h. The hot pressed scandium-containing sample is placed in a tubular furnace, heated to 700°C at 2°C / min in a nitrogen atmosphere, and maintained for 6h to obtain a carbon matrix containing scandium nitride. The above-mentioned carbon matrix containing scandium nitride is placed in a sulfuric acid solution with a concentration of 80%, treated at a temperature of 60°C, and oxidatively modified for 1 hour. The sample is washed with water, filtered until the pH is neutral, and dried to obtain a modified scandium-based carbon matrix. The modified scandium-based carbon matrix is ​​heated to 600°C at 2°C / min in an air atmosphere and maintained for 6 hours to remove residual carbon in the modified scandium-based carbon matrix and obtain scandium oxide nanoparticles.

[0081] The prepared negative electrode material was used to prepare a negative electrode sheet and a button-type half-cell was assembled for testing. The specific process is as follows.

[0082] The prepared scandium-based lithium-ion battery negative electrode material was weighed with conductive carbon black, sodium carboxymethyl cellulose, and styrene-butadiene rubber in a mass ratio of 94%:2%:3%:3%, and evenly mixed using a beater in an aqueous solvent. The battery slurry was coated on a copper foil, dried, cut into pieces, and assembled into button-type half-cells in a glove box, and their electrochemical properties were evaluated.

[0083] The electrochemical test mode is: the first week is 0.1C discharge to 0.005V, 0.05C discharge to 0.005V, 0.02C discharge to 0.005V. After standing for 5s, charge to 1V at 0.1C. The subsequent cycles are 0.5C discharge to 0.005V, 0.2C discharge to 0.005V, 0.05C discharge to 0.005V, 0.02C discharge to 0.005V, and charge to 1V at 0.5C after standing for 5s.

[0084] The discharge in the above electrochemical test is a lithium insertion process, corresponding to the charge in the full battery, and the charge in the above electrochemical test is a lithium removal process, corresponding to the discharge of the full battery.

[0085] After the prepared negative electrode material was coated on copper foil according to the above ratio, a 1Ah soft-pack battery was assembled with lithium cobalt oxide as the positive electrode, and its cycle performance at 0.5C was tested.

[0086] The test results of the first cycle efficiency and 100-cycle capacity retention rate of the half-cell prepared in this embodiment are recorded in Table 1.

[0087] Example 2

[0088] This embodiment provides a method for preparing a scandium-based negative electrode material and a performance test thereof. The specific preparation process is as follows.

[0089] Weigh 200g of scandium nitrate and dissolve it in 1800ml of deionized water to prepare a homogeneous solution with a concentration of 10%, add 77.9g of agar powder, and stir to mix evenly. Place the above solution in a constant temperature water bath, heat it to 100°C, and maintain it for 0.5h, so that the molecular chain of the coagulant breaks and dissolves, forming a cross-linked sol containing scandium ion solution. Subsequently, the sol is placed at room temperature and maintained for 12h to form a solid gel. The gel is placed under a hot press, maintaining the hot pressing curing pressure at 30MPa, the hot pressing temperature at 150°C, and the hot pressing time for 1h. The hot pressed scandium-containing sample is placed in a tubular furnace, heated to 1000°C at 10°C / min in a nitrogen atmosphere, and maintained for 2h to obtain a carbon matrix containing scandium nitride. The above-mentioned carbon matrix containing scandium nitride is placed in a nitric acid solution with a concentration of 60%, treated at a temperature of 20°C, and oxidatively modified for 6 hours. The sample is washed with water, filtered until the pH is neutral, and dried to obtain a modified scandium-based carbon matrix. The modified scandium-based carbon matrix is ​​heated to 800°C at 10°C / min in an air atmosphere and maintained for 2 hours to remove residual carbon in the modified scandium-based carbon matrix and obtain scandium oxide nanoparticles.

[0090] The obtained negative electrode material was used to prepare negative electrode sheets and button-type half-cells were assembled for testing. The assembly and testing methods were the same as those in Example 1.

[0091] The test results of the first cycle efficiency and 100-cycle capacity retention rate of the half-cell prepared in this embodiment are recorded in Table 1.

[0092] Example 3

[0093] This embodiment provides a method for preparing a scandium-based negative electrode material and a performance test thereof. The specific preparation process is as follows.

[0094] Weigh 200g of scandium nitrate and dissolve it in 800ml of deionized water to prepare a homogeneous solution with a concentration of 20%, add 194.6g of agar powder, and stir to mix evenly. The above solution is placed in a constant temperature water bath, heated to 90°C, and maintained for 0.75h, so that the coagulant molecular chain breaks and dissolves to form a cross-linked sol containing scandium ion solution. Subsequently, the sol is placed at room temperature and maintained for 12h to form a solid gel. The gel is placed under a hot press, maintaining the hot pressing curing pressure at 10MPa, the hot pressing temperature at 250°C, and the hot pressing time is 0.5h. The hot pressed scandium-containing sample is placed in a tubular furnace, heated to 800°C at 5°C / min in a nitrogen atmosphere, and maintained for 4h to obtain a carbon matrix containing scandium nitride. The above-mentioned carbon matrix containing scandium nitride is placed in a potassium permanganate solution with a concentration of 70%, treated at a temperature of 40°C, and oxidatively modified for 3 hours. The sample is washed with water, filtered until the pH is neutral, and dried to obtain a modified scandium-based carbon matrix. The modified scandium-based carbon matrix is ​​heated to 700°C at 5°C / min in an air atmosphere and maintained for 4 hours to remove residual carbon in the modified scandium-based carbon matrix and obtain scandium oxide nanoparticles.

[0095] The obtained negative electrode material was used to prepare negative electrode sheets and button-type half-cells were assembled for testing. The assembly and testing methods were the same as those in Example 1.

[0096] The test results of the first cycle efficiency and 100-cycle capacity retention rate of the half-cell prepared in this embodiment are recorded in Table 1.

[0097] Example 4

[0098] This embodiment provides a method for preparing a scandium-based negative electrode material and a performance test thereof. The specific preparation process is as follows.

[0099] Weigh 200g of scandium chloride and dissolve it in 1133ml of deionized water to prepare a homogeneous solution with a concentration of 15%, add 237.5g of agar powder, and stir to mix evenly. The above solution is placed in a constant temperature water bath, heated to 80°C, and maintained for 1h, so that the coagulant molecular chain breaks and dissolves to form a cross-linked sol containing scandium ion solution. Subsequently, the sol is placed at room temperature and maintained for 12h to form a solid gel. The gel is placed under a hot press, maintaining the hot pressing curing pressure at 15MPa, the hot pressing temperature at 180°C, and the hot pressing time for 2h. The hot pressed scandium-containing sample is placed in a tubular furnace, heated to 900°C at 3°C / min in a nitrogen atmosphere, and maintained for 3h to obtain a carbon matrix containing scandium nitride. The above-mentioned carbon matrix containing scandium nitride is placed in a potassium permanganate solution with a concentration of 60%, treated at a temperature of 50°C, and oxidatively modified for 4 hours. The sample is washed with water, filtered until the pH is neutral, and dried to obtain a modified scandium-based carbon matrix. The modified scandium-based carbon matrix is ​​heated to 750°C at 5°C / min in an air atmosphere and maintained for 3 hours to remove residual carbon in the modified scandium-based carbon matrix and obtain scandium oxide nanoparticles.

[0100] The obtained negative electrode material was used to prepare negative electrode sheets and button-type half-cells were assembled for testing. The assembly and testing methods were the same as those in Example 1.

[0101] The test results of the first cycle efficiency and 100-cycle capacity retention rate of the half-cell prepared in this embodiment are recorded in Table 1.

[0102] Example 5

[0103] This embodiment provides a method for preparing a scandium-based negative electrode material and a performance test thereof. The specific preparation process is as follows.

[0104] Weigh 200g of scandium chloride and dissolve it in 600ml of deionized water to prepare a homogeneous solution with a concentration of 25%, add 356.2g of carrageenan powder, and stir to mix evenly. The above solution is placed in a constant temperature water bath, heated to 80°C, and maintained for 1h, so that the molecular chain of the coagulant breaks and dissolves to form a cross-linked sol containing scandium ion solution. Subsequently, the sol is placed at room temperature and maintained for 12h to form a solid gel. The gel is placed under a hot press, maintaining the hot pressing curing pressure at 12MPa, the hot pressing temperature at 190°C, and the hot pressing time is 1.5h. The hot pressed scandium-containing sample is placed in a tubular furnace, heated to 900°C at 3°C / min in a nitrogen atmosphere, and maintained for 3h to obtain a carbon matrix containing scandium nitride. The above-mentioned carbon matrix containing scandium nitride is placed in a potassium permanganate solution with a concentration of 60%, treated at a temperature of 50°C, and oxidatively modified for 3 hours. The sample is washed with water, filtered until the pH is neutral, and dried to obtain a modified scandium-based carbon matrix. The modified scandium-based carbon matrix is ​​heated to 750°C at 5°C / min in an air atmosphere and maintained for 3 hours to remove residual carbon in the modified scandium-based carbon matrix and obtain scandium oxide nanoparticles.

[0105] The obtained negative electrode material was used to prepare negative electrode sheets and button-type half-cells were assembled for testing. The assembly and testing methods were the same as those in Example 1.

[0106] The test results of the first cycle efficiency and 100-cycle capacity retention rate of the half-cell prepared in this embodiment are recorded in Table 1.

[0107] Example 6

[0108] This embodiment provides a method for preparing a scandium-based negative electrode material and a performance test thereof. The specific preparation process is as follows.

[0109] Weigh 200g of scandium chloride and dissolve it in 1133ml of deionized water to prepare a homogeneous solution with a concentration of 15%, add 474.9g of carrageenan powder, and stir to mix evenly. The above solution is placed in a constant temperature water bath, heated to 80°C, and maintained for 1h, so that the coagulant molecular chain breaks and dissolves to form a cross-linked sol containing scandium ion solution. Subsequently, the sol is placed at room temperature and maintained for 12h to form a solid gel. The gel is placed under a hot press, maintaining the hot pressing curing pressure at 20MPa, the hot pressing temperature at 200°C, and the hot pressing time for 1.5h. The hot pressed scandium-containing sample is placed in a tubular furnace, heated to 700°C at 2°C / min in a nitrogen atmosphere, and maintained for 6h to obtain a carbon matrix containing scandium nitride. The above-mentioned carbon matrix containing scandium nitride is placed in a potassium permanganate solution with a concentration of 80%, treated at a temperature of 50°C, and oxidatively modified for 4 hours. The sample is washed with water, filtered until the pH is neutral, and dried to obtain a modified scandium-based carbon matrix. The modified scandium-based carbon matrix is ​​heated to 800°C at 5°C / min in an air atmosphere and maintained for 4 hours to remove residual carbon in the modified scandium-based carbon matrix and obtain scandium oxide nanoparticles.

[0110] The obtained negative electrode material was used to prepare negative electrode sheets and button-type half-cells were assembled for testing. The assembly and testing methods were the same as those in Example 1.

[0111] The test results of the first cycle efficiency and 100-cycle capacity retention rate of the half-cell prepared in this embodiment are recorded in Table 1.

[0112] Example 7

[0113] This embodiment provides a method for preparing a scandium-based negative electrode material and a performance test thereof. The specific preparation process is as follows.

[0114] Weigh 200g of scandium chloride and dissolve it in 400ml of deionized water to prepare a homogeneous solution with a concentration of 33.3%, add 415.5g of carrageenan powder, and stir to mix evenly. The above solution is placed in a constant temperature water bath, heated to 95°C, and maintained for 0.5h, so that the coagulant molecular chain breaks and dissolves to form a cross-linked sol containing scandium ion solution. Subsequently, the sol is placed at room temperature and maintained for 12h to form a solid gel. The gel is placed under a hot press, maintaining the hot pressing curing pressure at 30MPa, the hot pressing temperature at 150°C, and the hot pressing time for 2h. The hot pressed scandium-containing sample is placed in a tubular furnace, heated to 800°C at 2°C / min in a nitrogen atmosphere, and maintained for 5h to obtain a carbon matrix containing scandium nitride. The above-mentioned carbon matrix containing scandium nitride is placed in a potassium permanganate solution with a concentration of 80%, treated at a temperature of 80°C, and oxidatively modified for 2 hours. The sample is washed with water, filtered until the pH is neutral, and dried to obtain a modified scandium-based carbon matrix. The modified scandium-based carbon matrix is ​​heated to 750°C at 5°C / min in an air atmosphere and maintained for 6 hours to remove residual carbon in the modified scandium-based carbon matrix and obtain scandium oxide nanoparticles.

[0115] The obtained negative electrode material was used to prepare negative electrode sheets and button-type half-cells were assembled for testing. The assembly and testing methods were the same as those in Example 1.

[0116] The test results of the first cycle efficiency and 100-cycle capacity retention rate of the half-cell prepared in this embodiment are recorded in Table 1.

[0117] Example 8

[0118] This embodiment provides a method for preparing a scandium-based negative electrode material and a performance test thereof. The specific preparation process is as follows.

[0119] Weigh 200g of scandium sulfate pentahydrate and dissolve it in 800ml of deionized water to prepare a homogeneous solution with a concentration of 20%, add 384.1g of agar powder, and stir and mix evenly. The above solution is placed in a constant temperature water bath, heated to 80°C, and maintained for 1h, so that the coagulant molecular chain breaks and dissolves to form a cross-linked sol containing scandium ion solution. Subsequently, the sol is placed at room temperature and maintained for 12h to form a solid gel. The gel is placed under a hot press, maintaining the hot pressing curing pressure at 30MPa, the hot pressing temperature at 250°C, and the hot pressing time is 0.5h. The hot pressed scandium-containing sample is placed in a tubular furnace, heated to 1000°C at 10°C / min in a nitrogen atmosphere, and maintained for 3h to obtain a carbon matrix containing scandium nitride. The above-mentioned carbon matrix containing scandium nitride is placed in a sulfuric acid solution with a concentration of 80%, treated at a temperature of 60°C, and oxidatively modified for 2 hours. The sample is washed with water, filtered until the pH is neutral, and dried to obtain a modified scandium-based carbon matrix. The modified scandium-based carbon matrix is ​​heated to 650°C at 2°C / min in an air atmosphere and maintained for 5 hours to remove residual carbon in the modified scandium-based carbon matrix and obtain scandium oxide nanoparticles.

[0120] The obtained negative electrode material was used to prepare negative electrode sheets and button-type half-cells were assembled for testing. The assembly and testing methods were the same as those in Example 1.

[0121] The test results of the first cycle efficiency and 100-cycle capacity retention rate of the half-cell prepared in this embodiment are recorded in Table 1.

[0122] Example 9

[0123] This embodiment provides a method for preparing a scandium-based negative electrode material and a performance test thereof. The specific preparation process is as follows.

[0124] Weigh 200g of scandium sulfate pentahydrate and dissolve it in 1000ml of deionized water to prepare a homogeneous solution with a concentration of 16.7%, add 268.9g of gelatin powder, and stir to mix evenly. Place the above solution in a constant temperature water bath, heat it to 90°C, and maintain it for 0.75h, so that the molecular chain of the coagulant breaks and dissolves, forming a cross-linked sol containing scandium ion solution. Subsequently, the sol is placed at room temperature and maintained for 12h to form a solid gel. The gel is placed under a hot press, maintaining the hot pressing curing pressure at 25MPa, the hot pressing temperature at 220°C, and the hot pressing time for 1.5h. The hot pressed scandium-containing sample is placed in a tubular furnace, heated to 800°C at 4°C / min in a nitrogen atmosphere, and maintained for 3h to obtain a carbon matrix containing scandium nitride. The above-mentioned carbon matrix containing scandium nitride is placed in a nitric acid solution with a concentration of 80%, treated at a temperature of 50°C, and oxidatively modified for 5 hours. The sample is washed with water, filtered until the pH is neutral, and dried to obtain a modified scandium-based carbon matrix. The modified scandium-based carbon matrix is ​​heated to 800°C at 4°C / min in an air atmosphere and maintained for 3 hours to remove residual carbon in the modified scandium-based carbon matrix and obtain scandium oxide nanoparticles.

[0125] The obtained negative electrode material was used to prepare negative electrode sheets and button-type half-cells were assembled for testing. The assembly and testing methods were the same as those in Example 1.

[0126] The test results of the first cycle efficiency and 100-cycle capacity retention rate of the half-cell prepared in this embodiment are recorded in Table 1.

[0127] Example 10

[0128] This embodiment provides a method for preparing a scandium-based negative electrode material and a performance test thereof. The specific preparation process is as follows.

[0129] Weigh 200g of scandium oxalate and dissolve it in 1800ml of deionized water to prepare a homogeneous solution with a concentration of 10%, add 532.9g of pectin powder, and stir and mix evenly. The above solution is placed in a constant temperature water bath, heated to 100°C, and maintained for 1h, so that the coagulant molecular chain breaks and dissolves to form a cross-linked sol containing scandium ion solution. Subsequently, the sol is placed at room temperature and maintained for 12h to form a solid gel. The gel is placed under a hot press, maintaining a hot pressing curing pressure of 30MPa, a hot pressing temperature of 220°C, and a hot pressing time of 1h. The hot pressed scandium-containing sample is placed in a tubular furnace, heated to 900°C at 2°C / min in a nitrogen atmosphere, and maintained for 4h to obtain a carbon matrix containing scandium nitride. The above-mentioned carbon matrix containing scandium nitride is placed in a sulfuric acid solution with a concentration of 75%, treated at a temperature of 20°C, and oxidatively modified for 1.5 hours. The sample is washed with water, filtered until the pH is neutral, and dried to obtain a modified scandium-based carbon matrix. The modified scandium-based carbon matrix is ​​heated to 600°C at 2°C / min in an air atmosphere and maintained for 2 hours to remove residual carbon in the modified scandium-based carbon matrix and obtain scandium oxide nanoparticles.

[0130] The obtained negative electrode material was used to prepare negative electrode sheets and button-type half-cells were assembled for testing. The assembly and testing methods were the same as those in Example 1.

[0131] The test results of the first cycle efficiency and 100-cycle capacity retention rate of the half-cell prepared in this embodiment are recorded in Table 1.

[0132] Embodiment 11

[0133] This embodiment provides a preparation process and performance test of a negative electrode material, and the specific preparation process is as follows.

[0134] Weigh 200g of scandium nitrate and place it in a tube furnace. Heat it to 700℃ at 2℃ / min in a nitrogen atmosphere and maintain it for 6h to obtain a precursor containing scandium nitride. Place the above-mentioned precursor containing scandium nitride in a sulfuric acid solution with a concentration of 80%, treat it at a temperature of 60℃, and oxidize it for 1h. Wash the sample with water, filter it until the pH is neutral, and dry it to obtain a precursor containing scandium oxide. Heat the modified scandium-based carbon matrix to 600℃ at 2℃ / min in an air atmosphere and maintain it for 6h to obtain scandium oxide nanoparticles.

[0135] The obtained negative electrode material was used to prepare negative electrode sheets and button-type half-cells were assembled for testing. The assembly and testing methods were the same as those in Example 1.

[0136] The test results of the first cycle efficiency and 100-cycle capacity retention rate of the half-cell prepared in this embodiment are recorded in Table 1.

[0137] In order to better illustrate the effect of the embodiment of the present invention, a comparative example is compared with the above embodiment.

[0138] Comparative Example 1

[0139] This comparative example uses traditional nano silicon oxide particles as the negative electrode material.

[0140] The negative electrode material of this comparative example was used to prepare a negative electrode sheet and assembled into a button-type half-cell for testing. The assembly and testing methods were the same as those in Example 1.

[0141] The test results of the first cycle efficiency and 100-cycle capacity retention rate of the half-cell prepared in this comparative example are recorded in Table 1.

[0142] Table 1 below shows the electrochemical performance test comparison data of the negative electrode materials prepared in Examples 1-11 and Comparative Example 1.

[0143]

[0144]

[0145] Table 1

[0146] It can be seen from the test data in Table 1 that the first week coulomb efficiency and cycle capacity retention rate of Examples 1-11 are better than those of Comparative Example 1, because the preparation method of a scandium-based negative electrode material provided by the present invention is easy to control, safe and efficient. Scandium oxide nanoparticles have a cubic structure, and the advantages of physical and chemical properties are obvious. Its excellent thermal stability, chemical stability, high dielectric constant and low dielectric loss make the material have a high reversible charge and discharge specific capacity and cycle stability, and can exert excellent electrochemical performance. The present invention prepares scandium oxide nanoparticles by gel-hot pressing confined curing. When the scandium-containing compound and the coagulant are mutually dissolved to form a gel at room temperature, the overall dispersion and uniformity of the scandium-containing compound molecules are significantly improved, and the intermolecular forces and pressures generated during the evaporation of the solvent molecules during hot pressing curing make the material improve the dispersion of scandium ions while curing, forming a densely structured material. By modifying the surface oxidant solution, oxygen-containing functional groups are generated on the carbon matrix of the modified scandium-based carbon matrix, which can more easily remove carbon elements and carry away impurities in the material in the subsequent oxidation sintering and carbon removal process steps. Therefore, the scandium-based negative electrode material synthesized by the technical solution of the present invention is evenly dispersed and has high purity.

[0147] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a scandium-based negative electrode material, characterized in that: The preparation method comprises: Dissolving the scandium-containing compound in deionized water to prepare a homogeneous solution with a mass concentration of 10%-40%, adding a coagulant to the homogeneous solution, stirring and mixing to obtain a first solution; Placing the first solution in a heating device, heating it to 80° C.-100° C., and keeping it warm for 0.5 h-1 h, so that the molecular chains of the coagulant are broken and dissolved, so that the first solution forms a cross-linked sol containing a scandium ion solution; leaving the sol to stand at room temperature to obtain a solid gel; hot-pressing the solid gel to obtain a solidified sample in which scandium ions are uniformly dispersed; The solidified sample is placed in a tube furnace, and the temperature is raised to 700° C.-1000° C. at 2° C. / min-10° C. / min in a nitrogen atmosphere, and the temperature is kept for 2 h-6 h to obtain a carbon matrix containing scandium nitride; The carbon matrix containing scandium nitride is modified by soaking the carbon matrix containing scandium nitride in a surface oxidant solution with a concentration of 60%-80% at 20°C-60°C for 1h-6h, washing the modified sample with water, filtering it to a neutral pH, and drying it to obtain a modified scandium-based carbon matrix; or the carbon matrix containing scandium nitride is directly washed with water, filtered it to a neutral pH, and dried to obtain an unmodified scandium-based carbon matrix; wherein oxygen-containing functional groups are generated on the carbon matrix of the modified scandium-based carbon matrix; The modified scandium-based carbon matrix or the unmodified scandium-based carbon matrix is ​​heated to a set temperature at 2°C / min-10°C / min in an oxidizing atmosphere, and sintered for 2h-6h to remove residual carbon in the modified scandium-based carbon matrix to obtain scandium oxide nanoparticles.

2. The preparation method according to claim 1, characterized in that: The scandium-containing compound includes: one or more of scandium chloride, scandium nitrate, scandium sulfate, scandium oxalate and hydrates thereof; The coagulant includes: one or more of agar, carrageenan, gelatin, gum arabic or pectin; The mass ratio of the scandium element in the scandium-containing compound to the coagulant is 1:2-1:

10.

3. The preparation method according to claim 1, characterized in that: The standing time is 8-20 hours; The hot pressing pressure is 10MPa-30MPa, the temperature is 150°C-250°C, and the hot pressing time is 0.5h-2h.

4. The preparation method according to claim 1, characterized in that: The surface oxidant solution specifically includes one or more of potassium permanganate solution, nitric acid solution, and sulfuric acid solution; The chemical reactions occurring during the modification of the carbon matrix containing scandium nitride include: the scandium nitride in the carbon matrix containing scandium nitride undergoes an oxidation-reduction reaction with the surface oxidant solution to generate one or more of Sc2(SO4)3, Sc(NO3)3, and Sc2O3; and oxygen-containing functional groups are generated on the surface of the carbon matrix.

5. The preparation method according to claim 4, characterized in that: When the modified scandium-based carbon matrix is ​​sintered, when the surface oxidant solution used includes a sulfuric acid solution, the set temperature is 800° C.-1000° C.; When the surface oxidant solution used is potassium permanganate solution and / or nitric acid solution, the set temperature is 600° C.-800° C.; The oxidizing atmosphere includes air or oxygen; In an oxidizing atmosphere, in the modified scandium-based carbon matrix, residual carbon on the carbon matrix is ​​oxidized by oxygen to generate carbon dioxide. At the same time, Sc2(SO4)3 or Sc(NO3)3 present in the modified scandium-based carbon matrix is ​​thermally decomposed to form the scandium oxide nanoparticles.

6. The preparation method according to claim 5, characterized in that: When the surface oxidant solution used is a potassium permanganate solution, the byproduct of the redox reaction also includes MnO2, which exists on the surface of the scandium-based negative electrode material after sintering as a negative electrode coating of scandium oxide nanoparticles and / or exists in the scandium-based negative electrode material as an additive.

7. The preparation method according to claim 1, characterized in that: When the unmodified scandium-based carbon matrix is ​​sintered in an oxidizing atmosphere, the residual carbon on the carbon matrix is ​​oxidized by oxygen to generate carbon dioxide, and at the same time, the ScN in the unmodified scandium-based carbon matrix is ​​oxidized to form the scandium oxide nanoparticles.

8. A scandium-based negative electrode material prepared by any preparation method according to any one of claims 1 to 7.

9. A negative electrode plate for a lithium battery, characterized in that: The negative electrode plate of the lithium battery comprises the scandium-based negative electrode material as described in claim 8 above.

10. A lithium battery, characterized in that: The lithium battery comprises the lithium battery negative electrode plate as described in claim 9 above.

Citation Information

Patent Citations

  • Aluminum-magnesium acid scandium nano powder and preparation method thereof

    CN101693548A

  • Zirconium-scandium composite oxide-coated lithium titanate negative electrode material and preparation method therefor

    CN107293720A

  • Lithium battery diaphragm material and preparation method thereof

    CN113764825A

  • Ultrafine particle of scandium compound and its manufacture method

    JP2005082462A

  • Method of fabricating tungsten scandate NANO-composite powder for cathodes

    WO2016130580A1

Cited By

  • Alkaline zinc-manganese battery and preparation method thereof

    CN121394404A